A successful case of complete surgical resection via left upper and right lower lobectomy for bilateral lung metastases of a perivascular epithelioid cell tumor in the colon: a case report - Yoshinobu Fuse; Shohei Mori; Shun Sato; Daiki Kato; Takamasa Shibazaki; Takeo Nakada; Mitsuo Yabe; Hideki Matsudaira; Jun Hirano; Takashi Ohtsuka (Surgical Case Reports, 2021)
Abstract Background Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal neoplasms with malignant potential. No effective treatment other than surgical resection has been established for lung metastases of PEComas. We describe a patient who underwent complete surgical resection via bilateral lobectomy involving a two-step procedure for lung metastases 8 years after undergoing radical surgery for a colonic PEComa. Case presentation A 53-year-old woman underwent partial colectomy for a PEComa in the transverse colon 8 years ago. She presented with an abnormal chest shadow during a health examination. Chest computed tomography (CT) revealed a solid nodule 2 cm in diameter located centrally in the right lower lobe and a solid nodule 3 cm in diameter located centrally in the left upper lobe. Positron emission tomography revealed 18F-fluorodeoxyglucose uptake in these nodules. These nodules were suspected to be metastatic tumors of the colonic PEComa and were considered for complete surgical resection. Segmentectomy could not be performed because of the anatomical location of the tumors straddling the segments; therefore, bilateral lobectomy was required for complete surgical resection. Therefore, we performed two-step lobectomy safely with the expectation of pulmonary function recovery. Microscopically, the tumors were diagnosed as lung metastases of the PEComa. One year after the last surgery, no recurrence was detected, and the patient’s pulmonary function improved. Conclusions This case indicates that even if multiple lung metastases of a PEComa require bilateral lobectomy, complete resection with a two-step surgery may be considered.